Students’ Integrative Collaboration in the Early Youth in the Educational Establishments of the Construction Professional Direction - van Gejeka, Nataļja; Ignatjeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article presents the third part of a learning environment study in juvenile groups in Latvian a secondary technical school and deals with methodological aspects of learning environment organization in the context of students’ integrative collaboration. This study consists of three parts. The first part of the study reveals the presence of some organizational problems in teaching technical subjects in secondary technical schools related to the creativity of students. The second part of the study defines prevailing types of learning environments in technical schools and learners’ reactive anxiety levels regarding practical lessons. The third part clearly states how to create a learning environment with the goal of ensuring the conditions for student creative abilities development, widely using an integrative collaborative approach in the practical lessons of the technical discipline called Building Constructions at Riga Construction College’s school. Results show this approach failed to show a significant increase in student creativity.